Exhaust Temperature Control of Double Tail Flue Boiler - Wang Jinsong; Muhammad Akbar M (Jurnal Indonesia Sosial Teknologi, 2024)
According to the structural characteristics of a double tail flue boiler in a power plant, the cause of the fault was found through objective theoretical analysis, and corresponding improvement measures were formulated. The problem of abnormally high boiler exhaust temperature was effectively solved, the economy and safety of boiler operation were improved, and the normal operation of the boiler was ensured.